2004
DOI: 10.1007/s00213-003-1626-4
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of buprenorphine in conditioned place preference: temporal and pharmacological considerations

Abstract: The present results suggest that the reported lack of CPP effects at high doses of buprenorphine may be due to factors in the experimental design, resulting in a carry-over effect from drug- to vehicle conditioning. They also suggest that buprenorphine, like other opiates, produces its CPP effects via micro -receptors, although kappa-antagonistic mechanisms also appear to be involved. The implications of these findings for the safety of buprenorphine for human use are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Previous studies have shown that buprenorphine can induce psychomotor stimulation and reward (Rowlett et al, 1994;Smith et al, 2003;Sorge and Stewart, 2006;Sorge et al, 2005;Tzschentke, 2004). The results of the present study demonstrate that these actions of buprenorphine are mediated via the MOP.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have shown that buprenorphine can induce psychomotor stimulation and reward (Rowlett et al, 1994;Smith et al, 2003;Sorge and Stewart, 2006;Sorge et al, 2005;Tzschentke, 2004). The results of the present study demonstrate that these actions of buprenorphine are mediated via the MOP.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have shown that the presence of -opioid receptors is crucial for acquisition of naloxone-induced CPA because -opioid receptor knockout mice do not exhibit naloxone-induced CPA (Skoubis et al, 2001). In addition, it seems that partial agonist activity at -opioid receptors is sufficient to produce CPP because buprenorphine produces CPP (Tzschentke, 2004). Collectively, these findings suggest that the -opioid receptor is a critical component in mediating the oppositional CPP and CPA produced by opioid agonists and antagonists, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…One plausible explanation could be that the low efficacy of SR14150 at MOPr may not be sufficient to produce reward. However, other MOPr partial agonists with similar efficacies at MOPr, such as pentazocine and buprenorphine, have been shown to produce CPP comparable with that produced by morphine (Suzuki et al, 1991;Tzschentke, 2004;Marquez et al, 2007). It is possible that CPP could be induced with higher doses of SR14150; however, significantly higher doses were impossible to test because of loss of muscle tone at higher doses of SR14150.…”
Section: Discussionmentioning
confidence: 99%